Reactivities of iron(IV)-oxido compounds with pentadentate bispidine ligands - Bleher, Katharina; Comba, Peter; Kass, Dustin; Ray, Kallol; Wadepohl, Hubert (Journal of inorganic biochemistry, 2023)
The FeIV--O complexes of bispidines (3,7-diazabicyclo[3.3.1]nonane derivatives) are known to be highly reactive oxidants - with the tetradentate bispidine, the so far most reactive ferryl complex has been reported and two isomeric pentadentate ligands also lead to very reactive high-valent oxidants. With a series of 4 new bispidine derivatives we now try to address the question why the bispidine scaffold in general leads to very reactive oxidants and how this can be tuned by ligand modifications. The study is based on a full structural, spectroscopic and electrochemical analysis of the iron(II) precursors, spectroscopic data of the iron(IV)-oxido complexes, a kinetic analysis of the stoichiometric oxidation of thioanisole by five different bispidine-iron(IV)-oxido complexes and on product analyses of reactions by the five ferryl oxidants with thioanisole, beta-methylstyrene and cisstilbene as substrates.